Identifying the influencing factors for cataract surgery uptake in Malaysia - Mohamad Aziz Salowi; Nyi Nyi Naing; Ju Fan Tay; Wan Radziah Wan Nawang; Siti Nurhuda Sharudin; Norasyikin Mustafa; Nor Fariza Ngah (PLoS ONE, 2025)
Background/Aims In 2014, Malaysia conducted National Eye Survey II (NES II) using the World Health Organization (WHO)-recommended Rapid Assessment of Avoidable Blindness (RAAB) methodology across six administrative regions. The survey revealed significant discrepancies in key national eye care indicators, including prevalence of blindness, cataract surgery outcome, and effective Cataract Surgical Coverage (eCSC). In response, the Ministry of Health (MOH) launched the Klinik Katarak Kementerian Kesihatan Malaysia (KK-KKM) initiative, which includes mobile cataract surgical services to improve equitable access in the underserved areas in Sarawak and the Eastern Region. Despite endorsement and consistent operational funds, variations in cataract surgery uptake between regions persisted. We postulate that this disparity could be due to community-related factors and their interactions. In 2023, follow-up surveys were conducted in both regions to compare outcomes over time. The eligible subjects were consecutively recruited for a questionnaire interview. This study aims to identify the factors influencing cataract surgery uptake in Malaysia, specifically in Sarawak and Eastern Region. Methods A cross-sectional survey was carried out in 2023 using RAAB methodology, targeting individuals aged 50 years and above. Subjects with operable cataract with Pinhole Visual Acuity worse than 6/18, or a history of cataract surgery, were interviewed using the validated 22-item CatSurg-U questionnaire focused on Knowledge, Perception, Attitude and Practice. A total of 1,119 respondents (Sarawak: 408; Eastern 711) were recruited from 203 clusters. Binary logistic regression was used to identify demographic, socioeconomic and other predictors associated with non-uptake of cataract surgery. Results The identified factors that influenced individuals with unilateral operable cataracts to have “no surgery” in Sarawak included their “perception to own sight” [AOR: 0.67, 95% CI (0.53, 0.84) P = 0.001] and “attitude towards treatment” [AOR:1.47, 95% CI (1.17, 1.85) P = 0.001]. Meanwhile, in the Eastern region, the factors were “perception to own sight” [AOR: 0.80, 95% CI (0.69, 0.92) P = 0.002], “attitude towards treatment” [AOR:1.15, 95% CI (1.03, 1.29) P = 0.016], and “practice towards information” [AOR: 1.23, 95% CI (1.01, 1.50) P = 0.042]. For subjects with bilateral operable cataract in Sarawak, the factors that influenced them to have “no surgery” were “knowledge on surgery” [AOR: 0.35, 95% CI (0.25, 0.50) P < 0.001], “perception to own sight” [AOR: 1.48, 95% CI (1.15, 1.89) P  = 0.002], ethnicity (Chinese compared to Malays) [AOR: 0.19, 95% CI (0.04, 0.88) P = 0.033] and education level (primary school compared to secondary school or above) [AOR: 5.54, 95% CI (1.49, 20.69) P  = 0.011]. Additionally, for the Eastern region, the factors identified were “knowledge on surgery” [AOR: 0.35, 95% CI (0.26, 0.48) P < 0.001] and “practice on surgery” [AOR: 0.72, 95% CI (0.62, 0.84) P < 0.001]. Conclusion “Perception to own sight”, “attitude towards treatment”, and “knowledge on surgery” were key factors in both regions. Additional barriers in Sarawak include ethnicity and education levels, while in the Eastern Region, “practice towards information” and “practice on surgery” were key factors. Addressing these factors through targeted strategies such as enhancement of mobile outreach programs, public education, and service capacity expansion is essential. Collaborative efforts are needed to improve eye care delivery and ensure equitable access nationwide.